Prakriti In Ayurvedic Samhitas And Its Modern Genetic Correlates: A Critical Integrative Review - Kumar, Niraj; Day, Harnarayan; Mishra, Satendra Kumar (Journal of Neonatal Surgery, 2025)
Ayurveda, the ancient Indian system of medicine, emphasizes a personalized approach to health and disease management based on the concept of Prakriti—the inherent constitution of an individual formed at the time of conception. According to classical Ayurvedic texts such as Charaka Samhita, Sushruta Samhita, and Ashtanga Hridaya, Prakriti is primarily determined by the predominance of Tridoshas (Vata, Pitta, and Kapha) and remains constant throughout life, influencing an individual's physiological, psychological, and behavioral traits. In recent years, modern genomics has begun to uncover parallels with Ayurvedic concepts, suggesting a scientific basis for Prakriti-based personalized medicine. Several studies have shown correlations between Prakriti types and specific genetic markers such as HLA alleles, single nucleotide polymorphisms (SNPs), and genes involved in metabolic pathways like CYP2C19, ACE, and LEPR. These findings provide promising evidence that Prakriti phenotyping may align with genotypic variations and could serve as a foundation for predictive, preventive, and personalized medicine (PPPM). This integrative review critically explores the Prakriti concept as elaborated in Ayurvedic Samhitas and evaluates its potential genetic underpinnings through the lens of current biomedical research. By establishing a dialogue between traditional Ayurvedic wisdom and contemporary genomics, this review underscores the relevance of Prakriti in advancing a holistic and individualized approach to healthcare. It also identifies gaps in current knowledge and suggests directions for future research, including the development of standard Prakriti assessment tools and large-scale genomic validation studies.